Pemberdayaan Kelompok Wanita Tani Melalui Optimalisasi Pemanfaatan Pekarangan dengan Budidaya Sayuran Organik Dataran Rendah Berbasis Kearifan Lokal dan Berkelanjutan - Endang Warih Minarni; Darini Sri Utami; Nur Prihatiningsih (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2017)
The specific purpose of this activity is to increase the motivation of women in improving the quality of life and self-reliance in the family by optimizing the yard with organic vegetable farming in the lowlands based on Local Wisdom and Sustainable.  The strategy used was  the empowerment of target groups with the approach of Participatory Rural Appraisal, methods of education, training, demonstration plots, assistance and equipped with learning by doing techniques. The materials presented were: (1) garden  intensification technology with verticultur method, (2) organic vegetable cultivation technology based on liquid organic fertilizer, botanical pesticide and PGPR, (3) composting technology with enrichment of Trichoderma harzianum (Tricho-compos) activator of local microorganism, (4) technology of pest and disease control on environmentally friendly vegetable crops using botanical insecticides and microbial antagonists; (5) water use efficiency technology with drip irrigation; (6) good sorting, grading and packing technology, 7) empowerment technology to form groups and institutional strengthening and group management. The results of this activity are: (1) the target group / members The women farmer group has a very high curiosity about new information that can improve their standard of living,(2) technology transfer activities on the use of garden with organic vegetable cultivation received positive response from the members of the Group, (3) This devotional activity can encourage the pattern of mind and pattern of member action in organic vegetable cultivation by developing rural resources and sustainable local wisdom, (4) Verikultur cultivation technique with vertical paralon type on a land area of 10 m2 is economically profitable